Sustainable brain-inspired electronics: digging into natural biomaterials for healthcare applications - Paulin, João V. [UNESP]; Bufon, Carlos C. B. [UNESP] (Royal Society of Chemistry (RSC), 2024)
With traditional medical technologies shifting towards a more personalized point-of-view, current semiconductor-based electronics may need high-performance computing capability for cognitive and adaptive functions based on unspecific, multi-input, and complex tasks. Hence, developing electronic devices with improved capabilities is of utmost interest. One option takes inspiration from the synapse functionalities of the human brain. Due to their scalability and low power consumption, memristors and electrolyte-gated transistors are ideal candidates for efficient brain-inspired applications. Additionally, combining these device architectures with natural biomaterials (environmentally benign, biodegradable, biocompatible, and mechanically conformable) represents a new horizon toward transient and implantable synaptic devices. Here, we advertised the advances in artificial synaptic systems based on natural biomaterials and how these devices can be integrated into sustainable and intelligent healthcare systems. Our comprehensive review formulates the steps necessary for the next generation of healthcare electronics to flourish.